(untitled) (Studia theodisca, 2012)
In his comedy «Der neue Menoza», J. M. R. Lenz uses a love story between an exotic prince and a young German woman to simulate and debate a form of sexuality which the Bible disqualifies as incestuous. Inscribing a theological exegesis of incest as intertext in his framework, Lenz demonstrates the possibility of shifting this biblical taboo. Taking this perspective as the starting point of my investigation, I regard incest as a cultural construction. In the light of two contemporary discourses, the article points at the abrogation of the incest taboo by means of a re-writing of the biblical prohibition to be a sensitive issue in the cultural debate on sexuality.